3D printing in the apparel sector : how environmentally sustainable is it? - Carp, Belinda (Array, 2020)
3D printing is a process of making three dimensional (3D) solid objects from a digital file. The object is made using an additive process, which means that successive layers of material are laid down until the object is created. Each of these layers can be seen as a thinly sliced horizontal cross-section of the eventual object. The process enables complex shapes to be produced, using less material than in traditional manufacturing methods.3D printing processes are being used in manufacturing, medicine, architecture, custom art and design. Appli-cations in textiles range from fashion and sportswear to medical devices and aerospace.